Understanding digital TV the route to HDTV - Evans, Brian (IEEE Press, 1995)
This practical and concise handbook provides a fascinating and intuitive look into the field of digital television. An ideal book for the nontechnical person, "Understanding Digital TV" provides step-by-step examples of the concepts and the principles behind broadcast media.